TANGGUNG GUGAT PRODUCT LIABILITY DALAM HUKUM PERLINDUNGAN KONSUMEN DI INDONESIA - Adhitya Ariawan, Gede; Ari Yuliartini Griadhi, Ni Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013, 2013)
This paper shall be titled Liability Products under Consumer protection law inIndonesia, paper shall be apply the method of normative legal research in its writingprocess since it examines the general principles of law, the and its system. To protect therights of consumers who suffered losses due to a defective product manufactured by theproducer, a liability product with the principle of strict liability is required. Hence, thispaper shall be illustrate in broad outline the product liability with the principle of strictliability. Furthermore, also described the procedure for consumer in other to obtain thelegal protection against product defects and whether or not in the Law Number 8 Year1999regarding Consumer Protection, uphold the principle liability of strict liability within itsstipulation.
Keywords: Responsibility, Production, Producer, Consumer